2020
DOI: 10.3390/mi11020228
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the Sensing Margin of Silicon and Poly-Si 1T-DRAM

Abstract: Recently, one-transistor dynamic random-access memory (1T-DRAM) cells having a polysilicon body (poly-Si 1T-DRAM) have attracted attention as candidates to replace conventional one-transistor one-capacitor dynamic random-access memory (1T-1C DRAM). Poly-Si 1T-DRAM enables the cost-effective implementation of a silicon-on-insulator (SOI) structure and a three-dimensional (3D) stacked architecture for increasing integration density. However, studies on the transient characteristics of poly-Si 1T-DRAM are still l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
13
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 23 publications
2
13
0
Order By: Relevance
“…In our previous study, we proposed a method of optimizing the body thickness and bias conditions to simultaneously consider the memory performance and the short channel effects (SCEs) of a short-channel poly-Si 1T-DRAM cell [18]; we confirmed that thick body devices with a larger GB area have better memory performance than thin body devices because they have a larger amount of trapped charge. Also, in other studies, we verified that the sensing margin and retention time of a poly-Si 1T-DRAM cell are significantly affected by the number and location of the vertical GBs randomly determined during fabrication [15,17]. The memory performance of a poly-Si device in which a single GB is located near the source and drain is significantly reduced; the device's sensing margin is inversely proportional to the number of GBs in its body.…”
Section: Introductionsupporting
confidence: 72%
See 4 more Smart Citations
“…In our previous study, we proposed a method of optimizing the body thickness and bias conditions to simultaneously consider the memory performance and the short channel effects (SCEs) of a short-channel poly-Si 1T-DRAM cell [18]; we confirmed that thick body devices with a larger GB area have better memory performance than thin body devices because they have a larger amount of trapped charge. Also, in other studies, we verified that the sensing margin and retention time of a poly-Si 1T-DRAM cell are significantly affected by the number and location of the vertical GBs randomly determined during fabrication [15,17]. The memory performance of a poly-Si device in which a single GB is located near the source and drain is significantly reduced; the device's sensing margin is inversely proportional to the number of GBs in its body.…”
Section: Introductionsupporting
confidence: 72%
“…The inset in Figure 2 a shows trap densities according to band energy. We set the simulation trap parameter based on recent studies [ 15 , 16 , 17 , 18 ]. In the recent research of Reference [ 16 ], the investigators verified that the transient drain current is a function of the trap densities; donor type traps have little influence on the drain current while acceptor type trap densities are inversely proportional to the drain current.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations